The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ldr.3538
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of coastal marshes to croplands decreases organic carbon but increases inorganic carbon in saline soils

Abstract: Over the past century, conversion to agriculture has greatly reduced the global extent of coastal wetlands leading to degradation and loss of these ecosystems.However, it remains unclear how this land conversion affects the confluent soil organic and inorganic carbon (SOC and SIC) storage as well as their localizations in soil matrix. Here, we investigated these issues using wet sieving at two coastal saline-alkali sites in northern China. Conversion of marshes to cropland (>60 years) decreased the portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Particulate organic matter (POM, >53 μm) and mineralassociated organic matter (MOM, <53 μm) are distinct fractions in terms of their formation, spatial arrangement, persistence and functioning (Christensen, 2001;von Lützow et al, 2007;Wang et al, 2021). POM generally has a lower decomposition degree and higher carbon/nitrogen (C/N) ratio, which is more sensitive to biological and environmental changes (Lavallee et al, 2020;Y. Zhu et al, 2020); while the MOM has contrary features (Creamer et al, 2019;Hemingway et al, 2019;von Lützow et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate organic matter (POM, >53 μm) and mineralassociated organic matter (MOM, <53 μm) are distinct fractions in terms of their formation, spatial arrangement, persistence and functioning (Christensen, 2001;von Lützow et al, 2007;Wang et al, 2021). POM generally has a lower decomposition degree and higher carbon/nitrogen (C/N) ratio, which is more sensitive to biological and environmental changes (Lavallee et al, 2020;Y. Zhu et al, 2020); while the MOM has contrary features (Creamer et al, 2019;Hemingway et al, 2019;von Lützow et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Organic C status of salt–affected soils generally remains in low to medium category, while the inorganic C may vary depending on the climatic conditions, soil types, and management practices (Bhardwaj et al, 2019; Zhu et al, 2020). Poor performance of vegetation as a consequence of low return of root biomass facilitates slow SOC turnover and ultimately leads to low C storage (Bhardwaj et al, 2019; Wong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wu, Guo, and Peng (2003) assessed that land use change decreased SOC by approximately 7.1 Pg during 1997–2007 because of average SOC density decreases of 0.8 kg C m −2 for cultivated soils within semiarid/semihumid areas. Zhu et al (2020) showed that conversion (>60 years) of two marshes to cropland decreased SOC storage by up to 3.1‐times at 0–30 cm depth in Northern China. The conversion of peatland to flooded forest accelerates the decomposition of plant litter and SOC in tropical wetlands and thus influences SOC pools in wetlands (Sjögersten et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many investigations have evaluated the changes of SOC after the conversion of wetlands to agriculture (Wang, Wang, Feng, Guo, & Chen, 2014) and forestry activities (Ramesh et al, 2019), pastures (Steinman, Conklin, Bohlen, & Uzarski, 2003), aquaculture (Yang et al, 2018), and urbanization development (Pouyat, Yesilonis, & Nowak, 2006), but the depths of soil sampling in these studies were less than 30 cm (e.g., Chen, Arrouays, Angers, Martin, & Walter, 2019; Xu et al, 2017). Many of these studies have just compared SOC contents, fractions, aggregate‐associated organic C and stocks (e.g., dos Santos et al, 2019; Huo et al, 2018; Zhong et al, 2019; Zhu et al, 2020) rather than SOC sources, stability and the mechanisms controlling SOC turnover between wetlands and other land use types. For example, Huo et al (2018) found that dissolved organic carbon, microbial biomass carbon, readily oxidized carbon and readily mineralized carbon in a paddy field were lower than those in natural wetland by 13.8, 35.1, 59.0, and 17.9%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation